Effect of electron collisions with residual neutral gas on characteristic oscillation frequencies in systems of electron flows with a virtual cathode - Manuilenko, O.; Novikov, V.; Pashchenko, A.; Pashchenko, I.; Shapoval, I.; Yuferov, V. (Problems of Atomic Science and Technology, 2023)
A system of the hydrodynamic equations describing the electron flows in a diode with a virtual cathode is considered. Collisions are considered by introducing the corresponding braking force into the equations of motion. The stationary states of the electron flows are described. In a linear approximation, formulas are obtained for the frequencies of electron oscillations in a diode with a virtual cathode, considering the effective frequency of electron collisions. The expression for the decrement of oscillations due to the presence of collisions is obtained. Розглянуто систему гідродинамічних рівнянь, що описують потоки електронів у діоді з віртуальним катодом. Зіткнення введено у рівняння руху за допомогою відповідної гальмівної сили. Описано стаціонарні стани потоків електронів. У лінійному наближенні отримано формули для частот коливань електронів у діоді з віртуальним катодом з урахуванням ефективної частоти зіткнень електронів. Отримано вираз для декременту коливань через наявність зіткнень.